Evaluation of the Antibacterial Effect of Aurone-Derived Triazoles on Staphylococcus aureus - Csilla Klara Szepe; Arjun Kafle; Shrijana Bhattarai; Scott T. Handy; Mary B. Farone (MDPI AG, 2023)
Infections caused by antibiotic-resistant bacteria continue to pose a significant public health threat despite their overall decreasing numbers in the last two decades. One group of compounds fundamental to the search for new agents is low-cost natural products. In this study, we explored a group of newly synthesized novel aurone-derived triazole compounds to identify those with pharmaceutical potential as inhibitors of antibiotic-resistant Staphylococcus aureus. Using the broth microdilution method, antibacterial activities against methicillin-resistant S. aureus ATCC 43300 (MRSA) and methicillin-sensitive S. aureus ATCC 29213 (MSSA) were identified for four aurone-derived triazole compounds, AT106, AT116, AT125, and AT137, using the half-maximal inhibitory concentrations for the bacteria (IC50) and mammalian cell lines (CC50). Compounds AT125 and AT137 were identified to have pharmaceutical potential as the IC50 values against MRSA were 5.412 µM and 3.870 µM, whereas the CC50 values measured on HepG2 cells were 50.57 µM and 39.81 µM, respectively, resulting in selectivity indexes (SI) > 10. Compounds AT106 and AT116 were also selected for further study. IC50 values for these compounds were 5.439 µM and 3.178 µM, and the CC50 values were 60.33 µM and 50.87 µM, respectively; however, SI values > 10 were for MSSA only. Furthermore, none of the selected compounds showed significant hemolytic activity for human erythrocytes. We also tested the four compounds against S. aureus biofilms. Although AT116 and AT125 successfully disrupted MSSA biofilms, there was no measurable potency against MRSA biofilms. Checkerboard antibiotic assays to identify inhibitory mechanisms for these compounds indicated activity against bacterial cell membranes and cell walls, supporting the pharmaceutical potential for aurone-derived triazoles against antibiotic-resistant bacteria. Examining structure-activity relationships between the four compounds in this study and other aurone-derived triazoles in our library suggest that substitution with a halogen on either the salicyl ring or triazole aryl group along with triazoles having nitrile groups improves anti-Staphylococcal activity with the location of the functionality being very important.